Changing The Way of Life According to The Buddha Patihariya in Apaṇṇaka Sūtta - Ponsak, Thanisorn; vajiramethee, Phrarajvinaiya (Journal of Dhamma for Life, 2025)
This research aims to (1) examine the concepts and theories related to lifestyle transformation, (2) investigate the Buddhist miracles (Pāṭihāriya) as presented in the Apaṇṇaka Sutta, (3) integrate the principles of lifestyle transformation with the doctrinal insights derived from the Buddhist miracles in the Apaṇṇaka Sutta, and (4) propose a knowledge-based model for integrating these concepts into practical application. The study employed a qualitative research methodology, incorporating documentary research and in-depth interviews with 18 key informants, including Buddhist monks and recognized experts. The collected data were systematically analyzed, synthesized, and presented using descriptive analysis. The findings reveal that: (1) Theories of lifestyle transformation are grounded in psychology, sociology, and ethics, emphasizing the cultivation of self-awareness and disciplined personal development as core mechanisms for behavioral change. (2) The Buddhist miracles in the Apaṇṇaka Sutta emphasize the development of wisdom through doctrinal practices, particularly the Ten Wholesome Courses of Action (Kusala-kammapatha) and the Noble Eightfold Path, as fundamental frameworks for transforming behaviors, attitudes, and mindsets. (3) The integration of Buddhist miracles into lifestyle transformation is most effectively achieved through experiential learning, which facilitates a deep understanding and practical application of Buddhist teachings in daily life. (4) The proposed knowledge model highlights a process of transformative living and self-assessment for continuous personal growth, fostering sustainable changes in thought and behavior aligned with Buddhist principles. The research presents a systematic approach to lifestyle transformation through the CALLA Model, which provides a structured learning framework enabling individuals to comprehend, internalize, and apply Buddhist teachings in their personal and spiritual development. This model ultimately supports spiritual growth and the attainment of genuine well-being grounded in Buddhist wisdom.